Flow-induced polymer separation through a nanopore: effects of solvent quality. Issue 40 (20th September 2017) - Ding, Mingming; Duan, Xiaozheng; Shi, Tongfei
Abstract : Using a hybrid simulation method that combines a lattice-Boltzmann approach for the flow and a molecular dynamics model for the polymer, we investigated the effect of solvent quality on the flow-induced polymer translocation through a nanopore. Abstract : Using a hybrid simulation method that combines a lattice-Boltzmann approach for the flow and a molecular dynamics model for the polymer, we investigated the effect of solvent quality on the flow-induced polymer translocation through a nanopore. We demonstrate the nontrivial dependence of the translocation dynamics of polymers on the solvent quality, i.e., the enhancement in the polymer insolubility increases the critical velocity flux and shortens the translocation time. Accordingly, we propose a new strategy to separate polymers with different solubilities via their translocations in the nanopore by adjusting the velocity flux of the flow, which appears to be promising for the design of micro-scaled polymer separation devices.